Mechanism of chaperone action of small heat shock proteins - Vierling, Elizabeth (Henry Stewart Talks, 2007)
Small HSP diversity and evolution, Biological roles of sHSPs, sHSP structure and oligomeric assembly, Model of sHSP chaperone activity, sHSP oligomer dynamics, sHSP substrate interactions, Testing sHSP function in vivo
Archived at 2020/08/13